2017
DOI: 10.1103/physrevb.96.075142
|View full text |Cite
|
Sign up to set email alerts
|

Exact wave packet dynamics of singlet fission in unsubstituted and substituted polyene chains within long-range interacting models

Abstract: Singlet fission (SF) is a potential pathway for significant enhancement of efficiency in organic solar cells (OSC). In this paper, we study singlet fission in a pair of polyene molecules in two different stacking arrangements employing exact many-body wave packet dynamics. In the noninteracting model, the SF yield is absent. The individual molecules are treated within Hubbard and Pariser-Parr-Pople (PPP) models and the interaction between them involves transfer terms, intersite electron repulsions and site-cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Various strategies have been suggested for biasing the fate of S 1 (2 1 A g -) toward triplet production over internal conversion, such as engineering an enhanced ''triplet-pair'' weight into the S 1 (2 1 A g -) wavefunction with donor-acceptor copolymers, 26 and exploiting polymer-polymer interactions to extract long-lasting triplet states. 46,47 Interestingly, when SF does occur in systems expected to have relevant S 1 (2 1 A g -) states, the optical signatures of this intervening singlet are not observed, 18,[48][49][50][51][52] and its proposed role in fission remains controversial. 26,35,53,54 Although, several groups have shown that some polymers, all the way back to polyacetylene 35,39 have triplet-pair-like states similar to 2 1 A g -, 48,55 the general design strategy has been to avoid ''dark'' 2 1 A g states for efficient fission.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…Various strategies have been suggested for biasing the fate of S 1 (2 1 A g -) toward triplet production over internal conversion, such as engineering an enhanced ''triplet-pair'' weight into the S 1 (2 1 A g -) wavefunction with donor-acceptor copolymers, 26 and exploiting polymer-polymer interactions to extract long-lasting triplet states. 46,47 Interestingly, when SF does occur in systems expected to have relevant S 1 (2 1 A g -) states, the optical signatures of this intervening singlet are not observed, 18,[48][49][50][51][52] and its proposed role in fission remains controversial. 26,35,53,54 Although, several groups have shown that some polymers, all the way back to polyacetylene 35,39 have triplet-pair-like states similar to 2 1 A g -, 48,55 the general design strategy has been to avoid ''dark'' 2 1 A g states for efficient fission.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…On the other hand, molecular torsion of photoexcited polyenes has been suggested as a potential mechanism able to lower the rather strong triplet–triplet binding energy . Despite recent advances in the development of theoretical models, , much work is necessary in order to achieve a deep understanding of the intricacies and specificities of singlet fission in polyenes and carotenoids. In particular, there is still some debate on the nature of low-lying dark electronic states in carotenoids, which does not allow one to establish a well-defined singlet fission mechanism for these systems.…”
Section: Singlet Fission Materialsmentioning
confidence: 99%
“…Prodhan and Ramasesha conducted a quantum dynamics study on SF in polyenes . The polyenes include 1,3‐butadiene, 1,3,5‐hexatriene, and 1,3,5,7‐octatetraene.…”
Section: Exploration For Singlet Fission Mechanisms Through Dynamics mentioning
confidence: 99%